2010
DOI: 10.4103/0974-9233.71596
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and complications of traditional eye medications in Nigeria in a teaching hospital

Abstract: Purpose:The aim of this study was to determine the types and nature of traditional eye medications (TEMs), their sources, and the ocular complications that may arise from use in a teaching hospital in Nigeria.Materials and Methods:A prospective study of consecutive subjects who used TEM before presentation to the Eye Clinic of the University of Benin Teaching Hospital, Benin City, Nigeria between July 1, 2004 and June 30, 2008. P < 0.05 was considered statistically significant.Results:A total of 113 subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 8 publications
4
23
0
Order By: Relevance
“…The finding of preceding ocular trauma in 50% of patients in this study is similar to Oladigbolu's report of 51.3% in Nigeria [17] and that by Talukder et al [24] of 56.9% in Bangladesh but less than the 82.9% in West Bengal [20]. Corneal injury is a known predisposing factor for microbial keratitis [8] [9] [10] [11] [14] [15] [17] [20]- [25].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The finding of preceding ocular trauma in 50% of patients in this study is similar to Oladigbolu's report of 51.3% in Nigeria [17] and that by Talukder et al [24] of 56.9% in Bangladesh but less than the 82.9% in West Bengal [20]. Corneal injury is a known predisposing factor for microbial keratitis [8] [9] [10] [11] [14] [15] [17] [20]- [25].…”
Section: Discussionsupporting
confidence: 86%
“…The use of traditional eye medications (TEM) is still a common practice, as most patients in Africa consult a traditional healer before presentation to a hospital [25]. In this study, the use of TEM prior to presentation was noted in 50% of patients, demonstrating the high patronage of traditional healers in our locality, the rest of the patients had tried other forms of alternative medications, self medication and quackery.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The present study has shown that about 59.8% of respondents used eye medicines before coming to hospital. Self medication by people with ocular problems has been reported in several studies [10,11,12]. Eye problems that led to self medication are shown in table 2.…”
Section: Discussionmentioning
confidence: 89%
“…The application of home remedies such as herbal preparations, urine, breast milk, onions and kerosene to treat eye conditions is a common occurrence in Nigeria and other parts of Africa [11][12][13] . The consequence of this unorthodox practice is avoidable blindness often from significant corneal morbidity.…”
Section: Discussionmentioning
confidence: 99%